2021
DOI: 10.1111/joa.13538
|View full text |Cite
|
Sign up to set email alerts
|

Nasal asymmetry changes during growth and development in 6‐ to 12‐year‐old children with repaired unilateral cleft lip and palate: A 3D computed tomography analysis

Abstract: Repaired unilateral cleft lip and palate (UCLP) is often accompanied by the deformity and asymmetry of the nasal region. Three‐dimensional analysis was performed to investigate the relationship between nasal soft‐ and hard‐tissue asymmetries, as well as the changes in nasal asymmetry with age, among children with repaired UCLP (age: 6–12 years). Forty‐seven patients were included in this study. Their computed tomography records were retrieved for analysis of the 3D asymmetry of 10 landmarks of the nasal soft a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Gastrin is a peptide hormone released into the blood by the secretion of gastric fundus, with the element of 28 amino acids [ 21 ]. After acylation, it is able to combine with the growth hormone secretagogue receptor to across the blood-brain barrier, which is the only known hormone in the blood to stimulate appetite, with an unclear mechanism on promoting the GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin is a peptide hormone released into the blood by the secretion of gastric fundus, with the element of 28 amino acids [ 21 ]. After acylation, it is able to combine with the growth hormone secretagogue receptor to across the blood-brain barrier, which is the only known hormone in the blood to stimulate appetite, with an unclear mechanism on promoting the GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not evaluate nasal morphology, symmetry, and nostril support following alveolar bone grafting. Even though positive effects of bone graft on nasal symmetry and support have been reported in several studies,[ 13 14 15 ] a contrary publication suggested that mixed-dentition alveolar bone grafting appears to have no significant long-term effect on nasal morphology, symmetry, or nostril shape. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the anthropometric principle of Farkas, the malposition of the alare base has always been represented by the subalare ( 15 , 27 , 28 ). Traditional perspectives revealed that for a unilateral cleft lip, lateral and inferior deviation of the cleft alar base led to deformities.…”
Section: Nosementioning
confidence: 99%
“…These nasal changes might be attributed to the re-establishment of the muscle balance on both sides. After that, the nasolabial angle and columella could be corrected by growth and development ( 10 , 28 ). Since there was a lack of muscle in the area near the nasal tip, this region was susceptible to scar contracture, which resulted in a downward rotation of the columella and the nasal tip.…”
Section: Nosementioning
confidence: 99%
See 1 more Smart Citation